2019
DOI: 10.1101/669408
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coordination between stochastic and deterministic specification in the Drosophila visual system

Abstract: Many sensory systems use stochastic fate specification to increase their repertoire of neuronal types. How these stochastic decisions are coordinated with the development of their target post-synaptic neurons in processing centers is not understood. In the Drosophila visual system, two subtypes of the UV-sensitive R7 color photoreceptors called yR7 and pR7 are stochastically specified in the retina. In contrast, the target neurons of photoreceptors in the optic lobes are specified through a highly deterministi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(51 citation statements)
references
References 62 publications
2
48
1
Order By: Relevance
“…CC-BY 4.0 International license available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is made The copyright holder for this preprint this version posted October 4, 2020. ; https://doi.org/10.1101/2020.10.02.323477 doi: bioRxiv preprint interactome partner pairs mediating these critical functions (CARRILLO et al 2015;TAN et al 2015;BARISH et al 2018;XU et al 2018;ASHLEY et al 2019;COURGEON AND DESPLAN 2019;MENON et al 2019;VENKATASUBRAMANIAN et al 2019;XU et al 2019). Our screen to identify morphological or synaptic changes in fru P1 ∩ DIP-α and DIP-δ neurons, using dpr/DIP RNAi or overexpression transgenes identified only one perturbation with an impact; reduction of DIP-ε by RNAi on the fru P1 ∩ DIP-α pattern, with both cell autonomous and non-autonomous roles.…”
Section: Role Of Dprs and Dips In Sexual Dimorphism Of Fru P1 Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…CC-BY 4.0 International license available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is made The copyright holder for this preprint this version posted October 4, 2020. ; https://doi.org/10.1101/2020.10.02.323477 doi: bioRxiv preprint interactome partner pairs mediating these critical functions (CARRILLO et al 2015;TAN et al 2015;BARISH et al 2018;XU et al 2018;ASHLEY et al 2019;COURGEON AND DESPLAN 2019;MENON et al 2019;VENKATASUBRAMANIAN et al 2019;XU et al 2019). Our screen to identify morphological or synaptic changes in fru P1 ∩ DIP-α and DIP-δ neurons, using dpr/DIP RNAi or overexpression transgenes identified only one perturbation with an impact; reduction of DIP-ε by RNAi on the fru P1 ∩ DIP-α pattern, with both cell autonomous and non-autonomous roles.…”
Section: Role Of Dprs and Dips In Sexual Dimorphism Of Fru P1 Neuronsmentioning
confidence: 99%
“…Additionally, some Dprs interact dimerically with Dprs through either heterophilic or homophilic interactions, and some of the DIPs interact dimerically through homophilic interactions (OZKAN et al 2013;CARRILLO et al 2015;COSMANESCU et al 2018)(summarized in Supplemental Table 1). Functional analyses of the Dprs and DIPs have revealed roles in synaptic connectivity and specificity of neuronal targeting in the Drosophila neuromuscular junction, visual system and olfactory system (CARRILLO et al 2015;TAN et al 2015;BARISH et al 2018;XU et al 2018;ASHLEY et al 2019;COURGEON AND DESPLAN 2019;MENON et al 2019;VENKATASUBRAMANIAN et al 2019;XU et al 2019). Cell adhesion molecules have already been shown to be important for sculpting dimorphism in fru P1 neurons, with studies of the IgSF member encoded by roundabout (robo) shown to be a direct target of Fru M and responsible for dimorphic projections and morphology (MELLERT et al 2010;ITO et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This is only partially true because chance or contingency play an important role in evolution but vital determinism and nonrandom processes, such as recombination or epigenetic changes, also contribute to genomic changes. A proof of this was the recent report showing that there is coordination between stochastic and deterministic specification in the neurodevelopment of Drosophila visual system [51].…”
Section: The Evolutionary Imperativementioning
confidence: 84%
“…Another prediction of the matching hypothesis is that restoring Loaf to Dm8 cells in a loaf mutant background would result in a mismatch between R7 and Dm8, similar to removing loaf from R7 in a wild-type background ( Figure 3F). We tested this by expressing UAS-Loaf-HA in loaf mutant flies with the Dm8 drivers DIP-g-GAL4, tj-GAL4 and drifter (drf)-GAL4 (Carrillo et al, 2015, Courgeon and Desplan, 2019, Hasegawa et al, 2011, as well as a combination of tj-GAL4 and DIPg-GAL4. Again, we did not observe significant levels of R7 mistargeting ( Figure 3C…”
Section: Matching Loaf Levels In R7 and Its Major Synaptic Target Dm8mentioning
confidence: 99%
“…(H) quantification of the percentage of R7 axons that failed to reach the M6 layer in the indicated genotypes. n=10 suggesting that Dm8 or another tj-GAL4 expressing neuron such as Dm11 (Courgeon and Desplan, 2019), which also projects to the M6 layer (Nern et al, 2015) ( Figure 5 -figure supplement 1D), may contribute to matching the levels of Loaf to its postsynaptic targets. However, Tm5a/b and Dm9 appear to play a more significant role ( Figure 5I).…”
Section: R7 May Match Its Loaf Levels With Multiple Synaptic Target Cmentioning
confidence: 99%